Produção de metabólitos bioativos por biotransformações de diterpenos abundantes na natureza e avaliação do potencial destes na germinação e no crescimento de L. sativa - Alessandra Duarte Rocha (2010)
This work comprises the isolation of kaurane diterpenes, kaurenoic (1) and grandiflorenic acids (2), of triterpene 3-friedelinol (77), of ent-3-angeloiloxi-caur-16-en-19-oic acid (78) and a mixture of -sitosterol (79) and estigmasterol (80) from vegetal species Wedelia paludosa and preparation, by chemical modification of 1 and 2, of ethyl ent-kaur-16-en-19-oate (81), ethyl ent-kaur-9(11),16-dien-19-oate (82),ethyl ent-16-oxo-17-norkauran-19-oate (83), ethyl ent-16-oxo-17-norkauran-9(11)-en-19-oate (84), ent-15-hydroxy-kaur-16-en-19-oic acid (85), ent-15-hydroxy-kaur-9(11),16-dien-19-oic acid (86) and ent-16-formyl-kaur-15-en-19-oic acid (87) derivatives. Subsequently, some derivatives obtained by synthesis and other products isolated from W. paludosa were submitted to biological modification with fungi Cephalosporium aphidicola, Fusarium proliferatum and Pestalotiopsis palustris aiming at isolating products with allelophatic potential on germination and growth of Lactuca sativa (lettuce) roots and stems. From the biotransformations the followingmetabolites were isolated: ent-16,17,19-trihydroxykaurane (92), ent-16,19-dihydroxy-kaurane (50), ent-3,15,16,19-tetrahydroxykaurane (93) and ent-2-hydroxy-16-oxo-17-norkauran-19-oic acid (94), ent-2,15-dihydroxy-kaur-16-en-19-oic acid (95), ent-2,3,16,17-tetrahydroxykauran-19-oic acid (96), which presented allelophatic activity. In Chapter 1 (Introduction) it is presented a bibliographic survey on diterpenes and allelopathy. In Chapter 2 (Experimental part) it is described the methodology for the isolation of natural products from W. paludosa, preparation of kaurane derivatives and biotransformations performed. Chapter 3 (Results and discussion) reports thespectrometric analysis (IR, 1H and 13C NMR and MS) of the substances obtained of W. paludosa, of all substances used as starting materials and products of the chemical and biological reactions. In Chapter 4 (Biological assays) the results of bioassays carried out are showed: allelophatic biological activity on germination and growth of L. sativa (lettuce) and tests for acetylcholinesterase inhibition and antimicrobial activity